Public administration in troubled waters: organisations, management and `A New Oceania' - Thynne, Ian (1996)
The crux of this article is that public administration is indeed in troubled waters in terms of the threatened legitimacy of the modern state: that many of the organisational and managerial reforms of recent years have had the effect of debasing parliamentary politics by ushering in a much more definite form of executive imperialism than has ever been witnessed in previous eras. More specifically, the reforms have changed, or are changing, the configurations of power and authority in and beyond government in ways that appear to enhance neither the processes of democratic rule nor the individual and collective well-being of many sections of society. It is thus surely time to stand back, to take stock of the situation, and to question whether the reforms are in fact achieving goals and objectives to which governments and communities ought really to be committed. - Reproduced
Keywords: Public administration